Synthesis, antimicrobial activity studies and molecular property predictions of schiff bases derived from ortho-vanillin - Berk, Barkın; Ertaş, Merve; Biltekin, Sevde Nur (University of Istanbul, 2017)
Schiff bases are known to possess anticancer, antibacterial, antifungal, antitubercular, anti-inflammatory, antibacterial and antimalarial properties. At the same time, in recent years, prediction of drug-likeness, molecular, absorption, distribution, metabolism, and excretion (ADME) properties using in silico techniques has become a standard procedure for the evaluation of clinical usable molecules. In this study, Schiff base structured 2-methoxy-6-{[(2-alkyl/arylethyl)imino]methyl}phe-nol derivatives were synthesized from 3-methoxysalicylaldehyde (o-vanillin). The antibacterial and antifungal activities of these compounds were determined against Staphylococcus aureus, Escherichia coli, Candida albicans and Pseudomonas aeruginosa using agar-well diffusion and broth microdilution techniques. Further analysis was conducted using the in silico technique to predict the drug-likeness, molecular and ADME properties of these molecules. Among all the compounds, 2-{[(4-fluorophenethyl)imino]methyl}-6-methoxyphenol (Compound 9) exhibited the highest activity with good minimum inhibition concentration and radius of inhibition zone values against Candida albicans.
Keywords: Antifungal; Candida Albicans; In Silico; Molecular Properties; Schiff Bases